2017
DOI: 10.3892/etm.2017.4064
|View full text |Cite
|
Sign up to set email alerts
|

Association of nNOS and Rho-kinase with age-associated erectile dysfunction in Sprague-Dawley rats

Abstract: Abstract. The present study aimed to investigate the changes of Rho-associated kinase (Rho-kinase) and neuronal nitric oxide synthase (nNOS) expression in age-associated erectile dysfunction (ED) in Sprague-Dawley (SD) rats. A total of 100 intact male SD rats were divided into 20 groups according to their age (5-24 months; rats that were the same age in months were in the same group). Erectile response measurements were performed and the functional index intracavernosal pressure/mean arterial pressure (ICP/MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Erectile dysfunction (ED) is a prevailing health problem that compromises the quality of life of men and their partners (Shamloul & Ghanem, ). It was reported that aging is an independent predictor of ED, irrespective of comorbid diseases (Ding et al ., ). The Massachusetts Male Aging Study demonstrated that the annual incidence rate of ED was 1.2% in men aged between 40 and 49 years and the rate increased to 4.6% in men aged between 60 and 69 years (Johannes et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Erectile dysfunction (ED) is a prevailing health problem that compromises the quality of life of men and their partners (Shamloul & Ghanem, ). It was reported that aging is an independent predictor of ED, irrespective of comorbid diseases (Ding et al ., ). The Massachusetts Male Aging Study demonstrated that the annual incidence rate of ED was 1.2% in men aged between 40 and 49 years and the rate increased to 4.6% in men aged between 60 and 69 years (Johannes et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…A related study showed a marked decline in eNOS protein expression with age, while the Rho-kinase protein level was increased and, in particular, the eNOS/Rho-kinase ratio decreased with age. 35 Involvement of Rho-kinase in ED pathogenesis was also evaluated by animal model with HF. 17 The results showed that the rats developed ED after ligation of the left anterior descending coronary artery, as demonstrated by decreased ICP/MAP responses.…”
Section: Resultsmentioning
confidence: 99%
“… Conclusion: Age-associated ED was therefore correlated with decreased eNOS and increased Rho-kinase. 35 Vasculogenic and post-radical prostatectomy induced ED in human subjects Samples were collected from individuals who undergo penile surgery for Peyronie’s disease and from men with ED who underwent penile prosthesis implantation. ED was categorized into vasculogenic and post-RP subtypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each nerve was stimulated for 60 seconds, and the maximal ICP generated with the corresponding MAP (the ICP/MAP ratio) was recorded for each side. 22…”
Section: Measurement Of Intracavernosal Pressure (Icp) and Mean Artmentioning
confidence: 99%